Teknologi Budi Daya Ikan Nila Bagi Kelompok Pembudidaya Ikan Di Kecamatan Kawali, Kabupaten Ciamis, Jawa Barat - Pramono Adi, Catur; Napitupulu, Romauli Julia (JURNAL KASTARA, 2024)
Naturally, greater agricultural output is necessary to satisfy society's growing demands. Increasing the density of stockings is one possible endeavor. The production of fish will increase with the stocking density in a cultivation container, which will also affect the amount of money made. While high fish density affects low growth and increased stress on fish, low density affects good growth and high survival rates but low production per area. Understanding the social and economic income activities of the cultivating and processing community in Nila Village, Banjarwaru Hamlet, Kawali District, Ciamis Regency, as well as the characteristics of the cultivator area—Banjarwaru Hamlet, Kawali District, Ciamis Regency—are the goals of this PKM activity. As a result of this effort, six groups of cultivators have been formed in Kawali Nila Village, Banjarwaru Hamlet, Kawali District, Ciamis Regency. Nila Village raises tilapia, a fish species that goes through three stages: hatching, nursery, and grow-out.